Increasing workload in Norwegian general practice – a qualitative study - Ellen Rabben Svedahl; Kristine Pape; Marlen Toch-Marquardt; Lena Janita Skarshaug; Silje-Lill Kaspersen; Johan Håkon Bjørngaard; Bjarne Austad (BMC Family Practice, 2019)
Abstract Background General practitioners (GPs) play a key role in securing and coordinating appropriate use of healthcare services, by providing primary and preventive healthcare and by acting as gatekeepers for secondary healthcare services. Historically, European GPs have reported high job satisfaction, attributed to high autonomy and good compatibility with family life. However, a trend of increasing workload in general practice has been seen in several European countries, including Norway, leading to recruitment problems and concerns about the well-being of both GPs and patients. This qualitative interview study with GPs and their co-workers aims to explore how they perceive and tackle their workload, and their experiences and reflections regarding explanations for and consequences of increased workload in Norwegian general practice. Methods We conducted seven focus groups and four individual interviews with GPs and their co-workers in seven GPs’ offices in Mid-Norway: three in rural locations and four in urban locations. Our study population consisted of 21 female and 12 male participants; 23 were GPs and 10 were co-workers. The interviews were analysed using systematic text condensation. Results The analysis identified three main themes: (1) Heavy and increasing workload – more trend than fluctuation?; (2) Explanations for high workload; (3) Consequences of high workload. Our findings show that both GPs and their co-workers experience heavy and increasing workload. The suggested explanations varied considerably among the GPs, but the most commonly cited reasons were legislative changes, increased bureaucracy related to documentation and management of a practice, and changes in patients’ expectations and help-seeking behaviour. Potential consequences were also perceived as varying, especially regarding consequences for patients and the healthcare system. The participants expressed concerns for the future, particularly in regards to GPs’ health and motivation, as well as the recruitment of new GPs. Conclusions This study found heavy and increasing workload in general practice in Norway. The explanations appear to be multi-faceted and many are difficult to reverse. The GPs expressed worries that they will not be able to provide the population with the expected care and services in the future.